Frequency-dependency/independency analysis of damping magnification effect provided by tuned inerter absorber and negative stiffness amplifying damper considering soil-structure interaction - Wang, Meng; Sun, Fei-Fei; Nagarajaiah, Satish; Li, Yan-Wen (Mechanical systems and signal processing, 2022)
•Experimental validation of frequency dependent/independent features of ID/NSD.•Highlighting the influence of frequency variation caused by SSI on the damping magnification of TVMD/NSAD.•Proposing unified optimal design method for TVMD/NSAD considering SSI. As passive control techniques, both inerter device (ID) and negative stiffness device (NSD) produce forces that have a phase delay of π from common springs, i.e., negative stiffness behavior, when subjected to harmonic excitations. Thus, these two are both able to assist the motion of viscous damper in typical tuned inerter-based or negative stiffness-based absorbers, like tuned viscous mass damper (TVMD) or negative stiffness amplifying damper (NSAD), leading to a damping magnification effect. However, the negative stiffness value of NSD is frequency-independent; while that value of ID is frequency-dependent. In this regard, ID and NSD will perform differently due to structural frequency variation caused by soil-structure-interaction (SSI), which in turn further affects the energy dissipation capabilities and the seismic performance of TVMD and NSAD. Based on these effects, this paper systematically compares and discusses the optimal design and seismic performance of TVMD and NSAD from the point of SSI.